Integrating spatial planning and flood risk management: A new conceptual framework for the spatially integrated policy infrastructure. (May 2016) - Ran, Jing; Nedovic-Budic, Zorica
Abstract: Flooding is a widely occurring natural hazard that noticeably damages property, people, and the environment. In the context of climate change, the integration of spatial planning with flood-risk management has gained prominence as an approach to mitigating the risks of flooding. The absence of easy access to integrated and high-quality information, and the technologies and tools to use information are among the factors that impede this integration. Limited research has been conducted to develop a framework and to investigate the role of information and technologies in this integration. This study draws primarily on the European experiences and literature and identifies three dimensions of the integration of spatial planning with flood-risk management: territorial, policy, and institutional. To facilitate integration and in accord with these three dimensions, a Spatially Integrated Policy Infrastructure (SIPI) is conceptualised that encompasses data and information, decision support and analysis tools, and access tools and protocols. This study presents the connections between SIPI elements and integration dimensions, which is important for a better understanding of roles of geographic information and technologies in integration. The conceptual framework of SIPI will govern further development and evaluation of SIPI. Highlights: Integration of spatial planning and flood-risk management has three dimensions: territorial, policy and institutional. Developing infrastructures sharing both data and models and systems is a promising way to support integration. This paper conceptualises the Spatially Integrated Policy Infrastructure (SIPI) which focuses on policy integration.